Disadvantages of interfragmentary shear on fracture healing—mechanical insights through numerical simulation. Issue 7 (20th March 2014) - Steiner, Malte; Claes, Lutz; Ignatius, Anita; Simon, Ulrich; Wehner, Tim
ABSTRACT The outcome of secondary fracture healing processes is strongly influenced by interfragmentary motion. Shear movement is assumed to be more disadvantageous than axial movement, however, experimental results are contradictory. Numerical fracture healing models allow simulation of the fracture healing process with variation of single input parameters and under comparable, normalized mechanical conditions. Thus, a comparison of the influence of different loading directions on the healing process is possible. In this study we simulated fracture healing under several axial compressive, and translational and torsional shear movement scenarios, and compared their respective healing times. Therefore, we used a calibrated numerical model for fracture healing in sheep. Numerous variations of movement amplitudes and musculoskeletal loads were simulated for the three loading directions. Our results show that isolated axial compression was more beneficial for the fracture healing success than both isolated shearing conditions for load and displacement magnitudes which were identical as well as physiological different, and even for strain‐based normalized comparable conditions. Additionally, torsional shear movements had less impeding effects than translational shear movements. Therefore, our findings suggest that osteosynthesis implants can be optimized, in particular, to limit translational interfragmentary shear under musculoskeletal loading. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:865–872, 2014.